Community Empowerment Through Waste Bank Management to Achieve Sustainable Urban Development: A Case Study in Cilandak District, South Jakarta, Indonesia - Masruroh Masruroh; Abdul Rozak (Universitas Negeri Gorontalo, 2025)
Urban waste challenges persist in intensifying and numerous communities exhibit a lack of engagement regarding sustainable waste management practices, waste banks present an alternative, proactive approach that empowers individuals through collaborative waste governance. The purpose of this study is to find out: How are Community Empowerment Efforts in managing Waste Banks in the area. This study uses a qualitative approach with the research location at the Waste Bank in Cilandak District. The management of waste banks in Cilandak sub-district is carried out by sub-districts in Cilandak sub-district, waste management is in accordance with Governor Regulation No. 77 of 2020 that each sub-district forms a waste bank up to the sub village level. Waste management in the Cilandak sub-district area has implemented the 3R concept, namely: a) Reduce (reduce waste generation), Reuse (reuse), and Recycle (recycle). The implementation of community empowerment through waste banks in Cilandak sub-district which is lowered into the activity program in each sub-district, namely having activities including waste bank socialization, waste saving, waste selection, skills training and evaluation carried out in the work program every year, but there are still shortcomings because not all RT/RW from each sub-district have formed a waste bank. This research is confined to one district and may not adequately represent wider regional disparities. Subsequent investigations ought to incorporate a comparative analysis across various urban locales to evaluate distinct frameworks of waste bank management and their enduring socio-economic and environmental repercussions.